2017
DOI: 10.3390/molecules22111886
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide II Inhibits Proliferation, Motility and Induces Apoptosis in Human Gastric Carcinoma Cell Lines HGC-27 and AGS

Abstract: Atractylenolide II (AT-II) exhibits several biological and pharmacological functions, especially anti-cancer activity as the major sesquiterpene lactones isolated from Atractylodes macrocephala (also named Baizhu in Chinese). However, the effects and mechanisms of AT-II on human gastric cancer remain unclear. Cell Counting Kit-8 (CCK-8) assay, morphological changes, flow cytometry, wound healing assay and Western blot analysis were used to investigate the effects of AT-II on cell proliferation, apoptosis and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…A randomized controlled trial also verified the therapeutic effect of AT-1 on GC cachexia ( Liu et al, 2008 ). Similarly, for Atractylenolide II (AT-II), Bax expression could also be up-regulated, and B-cell lymphoma 2 (Bcl-2), phosphorylated protein kinase B (p-Akt), and phosphorylated ERK (p-ERK) expression could be down-regulated, which induced apoptosis and inhibited proliferation and migration of HGC-27 and AGS in a concentration- and time-dependent manner by inactivating Ras/ERK and PI3K/Akt signaling pathways ( Tian et al, 2017 ). AT-1 and AT-2 also inhibit Akt/IκBα/NF-κB signaling pathway to play a role, thereby inhibiting gastritis to GC transformation ( Amin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial also verified the therapeutic effect of AT-1 on GC cachexia ( Liu et al, 2008 ). Similarly, for Atractylenolide II (AT-II), Bax expression could also be up-regulated, and B-cell lymphoma 2 (Bcl-2), phosphorylated protein kinase B (p-Akt), and phosphorylated ERK (p-ERK) expression could be down-regulated, which induced apoptosis and inhibited proliferation and migration of HGC-27 and AGS in a concentration- and time-dependent manner by inactivating Ras/ERK and PI3K/Akt signaling pathways ( Tian et al, 2017 ). AT-1 and AT-2 also inhibit Akt/IκBα/NF-κB signaling pathway to play a role, thereby inhibiting gastritis to GC transformation ( Amin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 family members, Bax (proapoptotic) and Bcl-2 (antiapoptotic), are critical in the regulation of apoptotic cell death [ 19 , 20 ]. A change of the Bax/Bcl-2 ratio is known to ultimately activate the caspase family of proteins, such as caspase-9 and caspase-3 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…U87MG cells were seeded into each well at a density of 2 × 10 5 cells/mL in a 96well microplate. After 24 h, cells were suspended in the medium containing different concentrations of hispidulin (5,10,20,40, and 100 μg/ml), TMZ (50, 100, 200, 400, and 800 μM), or their combination TMZ (100 μg/ml of TMZ and 100 μg/ml of hispidulin) for 48 h. en, the cells were washed with PBS, and 10 μL MTT (5 mg/ml) was added to each well. Following 4 h incubation at 37 °C, the supernatant was discarded, and the formed formazan crystals in viable cells were lysed by adding DMSO (100 μl) in each well.…”
Section: Cell Viability Analysismentioning
confidence: 99%
“…Its main active ingredients include atractylenolide I, II and III [13]. Numerous studies have shown that atractylenolide I and II exhibited obvious anticancer and chemopreventive activities by significantly inhibiting the cell proliferation and inducing apoptosis and cell cycle arrest in various cancer cells [14][15][16][17][18][19]. However, the study is limited for the anticancer effect of atractylenolide III.…”
Section: Discussionmentioning
confidence: 99%